Analisis Spasial Kasus Malaria di Kabupaten Banyumas Tahun 2009-2018 - Destika Dhaniasri; Dwi Sarwani Sri Rejeki; Setyowati Raharjo (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2020)
Malaria is still a public health problem in the Banyumas district. Spatial information can be used as a strategy to control malaria. This study aimed to describe malaria cases using spatial analysis in the Banyumas District from 2009 to 2018 based on environmental conditions. This research was quantitative method conducted by a descriptive spatial approach. Data collected by secondary data which was obtained from various sources such as Health Agency, Statistics Indonesia, Indonesian Ministry of National Development, National Institute of Research and Development, and Office of Public Works of Banyumas. The data analysis implemented was descriptive and processed with ArcGis software. The findings illustrated that the number of malaria cases during the 2009-2018 period in Banyumas district was 1624 cases. The most dominant malaria cases distribution were in Sumpiuh and Tambak Subdistrict. The Trend of API from 2009 to 2018 was getting better, 2009 to 2012 found that there were subdistricts with Moderate Case Incidence (MCI) and High Case Incidence (HCI), however, Low Case Incidence (LCI) was present in 2013 to 2018 in Sumpiuh and Kebasen subdistricts and the rests were free from malaria. The results of spatial analysis discovered that most of the malaria cases were in the medium population density area. The distribution of malaria cases has decreased significantly, even though the environmental conditions still potentially transmit malaria.